Periocular implantation cysts: a late complication of ophthalmic surgery - Kalantzis, G K (Nature Publishing Group, 2014)
PURPOSE: To describe the clinical characteristics for a group of patients presenting with acquired implantation cysts following periocular surgery. METHODS: Retrospective, non-comparative series of patients who underwent surgery at Moorfields Eye Hospital for orbital implantation cysts, with review of clinical case notes and imaging. RESULTS: Twenty-three patients (13 male; 57%) were treated between 1997 and 2011 with cystic lesions that presented at an average interval of 22.7 years after previous periocular surgery. The age at presentation ranged from 14 to 76 years (mean 45.3; median 46 years). Five patients had a history of prior enucleation or evisceration (with ball implantation in 4/5 cases) and six had undergone orbital fracture repair with either a silicone or titanium plate. Eight patients had prior strabismus surgery, three had retinal detachment repair with either a scleral buckle or vitrectomy, and one patient had repair of a conjunctival laceration in childhood. All but one patient underwent either wide marsupialisation or complete excision of the implantation cysts, with no record of recurrence. Visual acuity improved after surgery in a half of the patients, whereas remaining unchanged in the remainder. CONCLUSION: Orbital implantation cysts constitute a relatively rare complication of periocular surgery and can present decades after the causative procedure.